2000
DOI: 10.1006/fmic.2000.0360
|View full text |Cite
|
Sign up to set email alerts
|

Zymological indicators: a new concept applied to the detection of potential spoilage yeast species associated with fruit pulps and concentrates

Abstract: In a survey of the microbial quality of raw materials used in fruit juice processing, yeast counts in fruit concentrates and pulps were found to range from 51to 2?9610 3 cfu g 71. Ascomycetous yeasts were represented by 76% of the isolates while 24% were basidiomycetes.The identi¢cation of strains isolated by the simpli¢ed identi¢cation system (SIM) revealed19 yeast species representing12 genera.The most frequently isolated yeasts belonged to the genera Saccharomyces, Pichia, Cryptococcus, Kluyveromyces and Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 24 publications
0
24
0
2
Order By: Relevance
“…For instance, Y. lipolytica has been detected in other fermented food products, such as tempeh and sourdough (Romano et al, 2006;Samson et al, 1987), in soft drinks, juices, wine, must and cider (Stratford, 2006), in fruits, fruit concentrates, vegetables and raw plant materials (Sancho et al, 2000), in mayonnaise, salad dressings and salads (Baleiras Couto et al, 1996), as well as in chilled and frozen, processed food, including seafood. All these examples suggest that Y. lipolytica may be a regular, although probably minor, component of food microbiota.…”
Section: Natural Occurrence Of Yarrowia Lipolytica In Foodmentioning
confidence: 99%
“…For instance, Y. lipolytica has been detected in other fermented food products, such as tempeh and sourdough (Romano et al, 2006;Samson et al, 1987), in soft drinks, juices, wine, must and cider (Stratford, 2006), in fruits, fruit concentrates, vegetables and raw plant materials (Sancho et al, 2000), in mayonnaise, salad dressings and salads (Baleiras Couto et al, 1996), as well as in chilled and frozen, processed food, including seafood. All these examples suggest that Y. lipolytica may be a regular, although probably minor, component of food microbiota.…”
Section: Natural Occurrence Of Yarrowia Lipolytica In Foodmentioning
confidence: 99%
“…Sin embargo las pruebas fisiológicas y bioquímicas siguen siendo desarrolladas y usadas. Así, los métodos de identificación simplificados (SIM) adaptados y publicados por Deak and Beuchat, 1996, fueron recientemente muy bien empleados para levaduras aisladas de jugos de frutas (Sancho et al, 2000). Velásquez et al,(2001) presentaron un sistema para la identificación de levaduras en productos alimenticios, mediante el uso de kit de 10 pruebas para levaduras vínicas.…”
Section: 32-aislamiento De Levaduras a Partir De Jugo Fermentadounclassified
“…Both are urease positive (Table 1, Figure 1), which matches Chen et al (2010) for the urea hydrolysis test. Beckenkamp (1997), when working with pasteurized fruit pulp samples, also identified the genera Rhodotorula & Trichosporon, while Sancho et al (2000) identified R. mucilaginosa in pear pulp. Guamán-Burneo & Carvajal-Barriga (2009), while working with different yeasts species of the genus Rhodotorula, found different salmon and pink hues for R. mucilaginosa cultured in CPM agar for 72 h at 20, 30, and 37 °C.…”
Section: Yeast Identificationmentioning
confidence: 99%
“…This enzyme has been long known and many consider the activity in the batch culture supernatant, here called CI, an extracellular invertase, including invertase from A. parasiticus (Lucca et al, 2013), from A. ochraceus (Guimarães et al, 2007), and from Penicillium chrysogenum (Poonawalla et al, 1965). According to Myers et al (1997), the expression of the gene that codes invertase is repressed at high free glucose concentrations. In this research, high free glucose concentration was only observed in the beginning of the log phase, which may be related to the low CI activity observed after 24 h of fermentation (Table 2).…”
Section: Assessing the Invertase Production By S Cerevisiae In Batchmentioning
confidence: 99%
See 1 more Smart Citation